Fear of public speaking for future pre-service teachers from first, second, and third semester of the bilingualism degree (2024)
This research explored the phenomena of fear of public speaking among students from the first, second, and third semesters of the bilingualism degree at a private university in Bogota. As researchers, we have identified that during the first semesters of our career, there was a lot of fear of public speaking from us and from our classmates, thus we decided to do the research using this big problem in our field. Furthermore, examined how emotions and second language learning affected how the students performed their speaking in English. The participants were 22 students from the Bilingualism program and teachers in charge of English I and II classes. We used focus groups, semi-structured interviews, and surveys for our data collection instruments. Therefore, the results suggested that the population fear public speaking since they tend to feel anxious, and nervous, and have physical and mental symptoms. They also expressed how important it is for them to be proficient in the target language. The results were discussed in terms of three main categories (self confidence as a bridge to foster public speaking, context as an ESL promoter, and English proficiency as a factor of fear in public speaking). Additionally, as an outcome of our research, we created a bank of strategies in which the students from these semesters can use, and for future researchers' needs.